Comprehensive In Situ Analysis of Arteriolar Network Geometry and Topology in Rat Gluteus Maximus Muscle. (August 2016) - Al Tarhuni, Mohammed; Goldman, Daniel; Jackson, Dwayne N.
Abstract: Objectives: To provide detailed geometric and topological descriptions of the rat gluteus maximus arteriolar network, and to measure the distribution of diameters and lengths as well as their associated variability within and between networks. Methods: Complete arteriolar networks arising from feed artery (inferior gluteal artery) to terminal branches were imaged under baseline conditions, using IVVM. Photomontages of complete networks were assembled and evaluated offline for measurements of geometry and topology. Single‐line (skeletonized) tracings of the networks were made for fractal analysis. Results: Diameters and lengths decreased with increasing topological order (centrifugal), while number of elements increased with increasing order. Horton's laws were shown to be valid within the arteriolar networks of the rat GM. Inter‐network variability in diameter (~5–22%) and length (~17–30%) at each order was generally lower than the corresponding intra‐network variability in diameter (~10–48%) and length (~39–106%). Conclusions: Data presented in this study provide crucial quantitative analysis of complete arteriolar networks within healthy skeletal muscle, and may serve as ideal experimental inputs for future theoretical studies of skeletal muscle microvascular structure and function.